2021
DOI: 10.21203/rs.3.rs-143372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potassium Phosphite Modulated the Soil Microbiome and Enriched the Antagonistic Bacteria Streptomyces Coelicoflavus and Paenibacillus Favisporus to Inhibit the Tomato Pathogen Ralstonia Solanacearum Synergistically

Abstract: Background: Application of certain agricultural chemicals could modulate the soil microbiome and induce potential antagonistic microbes. However, the specific selective effects of agricultural chemicals on soil bacterial functions and their co-occurrences are not well understood, and no studies have verified that the enriched potential antagonistic microbes could enhance the antagonistic functions of the soil microbiome.Results: Here, the effects of potassium phosphite (KP), an environment-friendly agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…NPA also increased the content of phytoalexin, phenolic components, flavonoids, anthocyanins and the enzymatic activity of phenylalanine ammonia-lyase (PAL) [66,67]. However, studies have reported that NPA alters the rhizosphere microbiome [68] and enriches antagonistic bacteria that inhibit plant pathogens [69]. The evidence provided in this study shows that NPA does not alter the cucumber phyllosphere microbial community, and this finding supports the specific activity of NPA as a plant defense elicitor.…”
Section: Plos Onesupporting
confidence: 61%
“…NPA also increased the content of phytoalexin, phenolic components, flavonoids, anthocyanins and the enzymatic activity of phenylalanine ammonia-lyase (PAL) [66,67]. However, studies have reported that NPA alters the rhizosphere microbiome [68] and enriches antagonistic bacteria that inhibit plant pathogens [69]. The evidence provided in this study shows that NPA does not alter the cucumber phyllosphere microbial community, and this finding supports the specific activity of NPA as a plant defense elicitor.…”
Section: Plos Onesupporting
confidence: 61%
“…The addition of phosphite increased the abundance of soil bacteria, but the relative abundance of all the phyla was very similar across the treatments. Su et al ( 2021a ) examined the effects of phosphite on the microbiome of tomatoes and found it enhanced the abundance of Proteobacteria and Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%